Association Between Blood Cadmium Levels and Mortality in Peritoneal Dialysis. Issue 19 (May 2016) - Lee, Cheng-Chia; Weng, Cheng-Hao; Huang, Wen-Hung; Yen, Tzung-Hai; Lin, Ja-Liang; Lin-Tan, Dan-Tzu; Chen, Kuan-Hsing; Hsu, Ching-Wei
Abstract : Abstract: The negative impact of environmental exposure of cadmium has been well established in the general population. However, the effect of cadmium exposure in chronic peritoneal dialysis (PD) patients remains uncertain. A total of 306 chronic PD patients were included in this 36-month observational study. Patients were stratified into 3 groups by the tertile of baseline blood cadmium levels (BCLs): high (>0.244 μg/L, n = 101), middle (0.130–0.244 μg/L, n = 102), and low (<0.130 μg/L, n = 103) for cross-sectional analyses. Mortality rates and cause of death were recorded for longitudinal analyses. Patients in the high-BCL group were older, more likely to have diabetes mellitus, had lower levels of serum albumin and lower percentage of lean body mass than patients in the low-BCL group. A multivariate logistic regression analysis revealed that logarithmic transformed BCL was independently associated with a higher risk of low turnover bone disease (odds ratio = 3.8, P  = 0.005). At the end of the 36-month follow-up, 66 (21.6%) patients died. Mortality rates increased with higher BCLs ( P for trend = 0.005). A Cox multivariate analysis showed that, using the low-BCL group as the reference, the high-BCL group had increased hazard ratios (HR) for all-cause mortality in chronic PD patients after adjusting for related variables (HR = 2.469, 95% confidence interval = 1.078–5.650, P  = 0.043). In conclusion, BCL showed significant association with malnutrition and low turnover bone disease in chronic PD patients. Furthermore, BCL is an important determinant of mortality. Our findings suggest that avoiding environmental exposure to cadmium as much as possible is warranted in chronic PD patients.